Dexrazoxane prevents vascular toxicity in doxorubicin-treated mice - Dustin N. Krüger; Matthias Bosman; Emeline M. Van Craenenbroeck; Guido R. Y. De Meyer; Constantijn Franssen; Pieter-Jan Guns (Cardio-Oncology, 2024)
Abstract Background Doxorubicin (DOX) is used for breast cancer and lymphoma, but can cause cardiotoxicity, arterial stiffness, and endothelial dysfunction. We recently reported SERPINA3N as biomarker of cardiovascular toxicity in patients and mice. Dexrazoxane (DEXRA) is an FDA-approved drug that prevents DOX-induced cardiac toxicity in high-risk patients. However, the effect of DEXRA on vascular dysfunction during DOX treatment has not been documented. Therefore, here we investigated whether DEXRA protects against DOX-induced arterial stiffness, endothelial dysfunction, and SERPINA3N upregulation in tissue and plasma from mice. Methods Male C57BL6/J mice were treated with DOX (4 mg/kg), DEXRA (40 mg/kg), a combination (DEXRA + DOX), or VEHICLE (0.9% NaCl) weekly i.p. for 6 weeks (n = 8 per group). Cardiovascular function was measured in vivo by ultrasound imaging at baseline, weeks 2 and 6. Vascular reactivity was analyzed ex vivo in the thoracic aorta at week 6 and molecular analysis was performed. Results DEXRA prevented left ventricular ejection fraction decline by DOX (DEXRA + DOX: 62 ± 2% vs DOX: 51 ± 2%). Moreover, DEXRA prevented the increase in pulse wave velocity by DOX (DEXRA + DOX: 2.1 ± 0.2 m/s vs DOX: 4.5 ± 0.3 m/s) and preserved endothelium-dependent relaxation (DEXRA + DOX: 82 ± 3% vs DOX: 62 ± 3%). In contrast to DOX-treated mice, SERPINA3N did not increase in the DEXRA + DOX group. Conclusion Our results not only confirm the cardioprotective effects of DEXRA against DOX-induced cardiotoxicity but also add preservation of vascular endothelial cell function as an important mechanism. Moreover, the study demonstrates the potential of SERPINA3N as a biomarker for monitoring cardiovascular complications of DOX in high-risk patients.